Severe Pulmonary Hypertension as Initial Presentation of SLE: A Case Report and Literature Review - Rabia Kiani; Muhammad Danial Siddiqui; Hamza Tantoush (Case Reports in Rheumatology)
Severe pulmonary artery hypertension (PAH) is a rare initial presentation of systemic lupus erythematosus (SLE). SLE associated with PAH carries worse prognosis that isolated SLE. However, there has been improvement in mortality of the patients in the recent years owing to newer treatment options available. Early recognition remains of prime importance. We present here a case of young female who presented with severe pulmonary hypertension with right heart failure leading to cardiogenic shock and was found to have SLE. She was started on appropriate treatment; however, given the severity of her illness, the patient did not survive. This case highlights the importance of early recognition and prompt treatment of SLE-associated PAH, which might improve the survival rate in the patients.